2020
DOI: 10.1002/chem.202000989
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Directed Antibody Immobilization by Resorc[4]arene‐Based Immunosensors

Abstract: One of the main problems in the development of immunosensors is to overcome the complexity of binding antibody to the sensor surface. Most of immobilizing methods lead to a random orientation of antibodies with a lower binding site density and immunoaffinity. In order to control the orientation of antibody immobilization, several resorc[4]arene derivatives were designed and synthesized. After the spectroscopic characterization of resorc[4]arene self-assembled monolayers (SAMs) onto gold films, the surface cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 45 publications
(59 reference statements)
0
26
0
Order By: Relevance
“…This fact can be explained because the random immobilization procedure is generally affected by the steric hindrance caused by neighboring antibody molecules, lowering the Ab density. , To further investigate the role of the site-direct approach of the RW platform, the calibration curve of the antigen bound by the RW@Au@MNPs-modified electrodes was compared with those obtained with the random asset SPEs/MPA@Au@MNPs. As reported in Figure B, the site-direct approach has shown a significantly higher sensitivity than the random configuration (∼ 46 vs ∼18 μA mL ng –1 cm –2 ). , This improvement may be addressed to the optimized Ab orientation for the synergistic mechanism between host-guest interaction and dipolar momentum alignment; ,, hence a higher population of Abs is available for the antigen-binding. , …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This fact can be explained because the random immobilization procedure is generally affected by the steric hindrance caused by neighboring antibody molecules, lowering the Ab density. , To further investigate the role of the site-direct approach of the RW platform, the calibration curve of the antigen bound by the RW@Au@MNPs-modified electrodes was compared with those obtained with the random asset SPEs/MPA@Au@MNPs. As reported in Figure B, the site-direct approach has shown a significantly higher sensitivity than the random configuration (∼ 46 vs ∼18 μA mL ng –1 cm –2 ). , This improvement may be addressed to the optimized Ab orientation for the synergistic mechanism between host-guest interaction and dipolar momentum alignment; ,, hence a higher population of Abs is available for the antigen-binding. , …”
Section: Resultsmentioning
confidence: 94%
“…The supramolecular self-assembly of macrocycle-modified nanomaterials allows the formation of morphologically controlled or highly ordered arrays, which was an important feature for miniaturized systems. In this context, the use of modified Au@MNPs could play a key role in enhanced immunosensor development. Our previous work demonstrated that surface modification by properly functionalized resorcarene macrocycles allows the optimal Ab orientation favoring the “end-on” configuration. , In this previous work, we demonstrated that the introduction at the upper rim of thioether alkyl chains allows an optimal functionalization procedure of the gold sensor disk surface by forming SAMs via oxidative absorption. However, due to the poor water-solubility of these macrocycles, most of the resorcarene based-sensors are prepared or applied in organic solvents such as tetrahydrofuran, toluene, chloroform, dichloromethane, etc., which may bring environmental pollution and severely limits their potential applications in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most common immobilization routes, including adsorption and amine coupling, result in random orientation, as schematically illustrated in Figure 1B , limiting the binding site's accessibility [ 8 ]. Thus, it is highly desirable to direct a tail‐on antibody orientation on the surface, with the Fc region coupled to the surface and the antigen binding site towards the target solution (Figure 1B ) [ 25 ]. Covalent and oriented immobilization can be achieved by coupling via glycan moieties or using Fab’ fragment's thiol groups; the latter can be linked to maleimide‐modified surfaces or directly to gold surfaces [ 10 , 16 , 26 ].…”
Section: Immunosensorsmentioning
confidence: 99%
“…In such optical immune-biosensors, antibody immobilization is a crucial step because it should ideally maintain the antigen recognition ability as in solution [ 6 ]. Immobilization on a solid surface can be achieved in a random or site-oriented manner [ 7 ], but generally, only in the second instance is the antibody properly positioned to allow the most productive interaction of the fragment antigen-binding (Fab) with the analyte [ 8 , 9 ], thus optimizing the biosensor’s performances [ 10 ].…”
Section: Introductionmentioning
confidence: 99%